2019
DOI: 10.3389/fninf.2019.00028
|View full text |Cite
|
Sign up to set email alerts
|

Responsible Data Governance of Neuroscience Big Data

Abstract: Current discussions of the ethical aspects of big data are shaped by concerns regarding the social consequences of both the widespread adoption of machine learning and the ways in which biases in data can be replicated and perpetuated. We instead focus here on the ethical issues arising from the use of big data in international neuroscience collaborations. Neuroscience innovation relies upon neuroinformatics, large-scale data collection and analysis enabled by novel and emergent technologies. Each step of this… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 49 publications
0
40
0
Order By: Relevance
“…To illustrate, the HBP is, among other things, a big data integration and provision project (Fothergill et al 2019a). Data governance is therefore key to the project and to the development of the infrastructure.…”
Section: The Hbp's Approach To Rrimentioning
confidence: 99%
See 1 more Smart Citation
“…To illustrate, the HBP is, among other things, a big data integration and provision project (Fothergill et al 2019a). Data governance is therefore key to the project and to the development of the infrastructure.…”
Section: The Hbp's Approach To Rrimentioning
confidence: 99%
“…The HBP's final phase started in April 2020 and will end in 2023. We have provided detailed accounts of our work during the first 8 years elsewhere Aicardi et al 2018;Fothergill et al 2019a;Stahl et al 2019;Aicardi et al 2020;Salles and Farisco 2020). We have published Opinions on three topics: data protection and privacy (Salles et al 2021), responsible dual use (Aicardi, Bitsch, Bådum, et al 2021), and artificial intelligence (AI) (Aicardi, Bitsch, Burton, et al 2021).…”
Section: Stages Processes and Outcomes Of Rri In The Hbpmentioning
confidence: 99%
“…It is worth noting that a large-scale survey in Australia in 2020 indicated that 57.9% of end-users are not at all confident that most companies take adequate steps to protect user data. The significance of understanding and employing responsibility is an issue targeted in many studies (Chatfield et al, 2017;Fothergill et al, 2019;Jirotka et al, 2017;Pellé & Reber, 2015). Trust and control over BD + AI as an issue is reiterated by a recent ICO report demonstrating that most UK citizens do not trust organisations with their data (ICO, 2017).…”
Section: Medium-term Issuesmentioning
confidence: 99%
“…In the health field, for example, where the sensitivity of patient and health data is universally acknowledged, data management and data governance are explicitly seen as ways of ensuring ethical goals (Rosenbaum 2010, OECD 2017. The proximity of ethical concerns and data governance has also led to the development of data governance approaches that are explicitly developed around ethical premises (Fothergill et al 2019).…”
Section: Organisational Governancementioning
confidence: 99%